2013
DOI: 10.1177/070674371305800706
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms Associated with Brief Detention of Adult Asylum Seekers in Canada

Abstract: For asylum seekers, even brief detention is associated with increased psychiatric symptoms. Governments should consider the many viable alternatives to incarceration of asylum seekers, such as temporary placement in a supervised residential facility, to minimize the risks of psychological harm to this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…In addition, our study has shown that general stressful experiences, experiences with deportation and stressors from detention are related to PTSD symptomatology, supporting results of previous studies that indicated the relation between detention and mental health difficulties among asylum seekers (Cleveland & Rousseau, 2013;Steel et al, 2006). Negative self-perception of functioning is related to the number of general stressors, while stressful events experienced in contact with the local population are related to depressive symptomatology.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, our study has shown that general stressful experiences, experiences with deportation and stressors from detention are related to PTSD symptomatology, supporting results of previous studies that indicated the relation between detention and mental health difficulties among asylum seekers (Cleveland & Rousseau, 2013;Steel et al, 2006). Negative self-perception of functioning is related to the number of general stressors, while stressful events experienced in contact with the local population are related to depressive symptomatology.…”
Section: Discussionsupporting
confidence: 89%
“…Our studies have shown that detention negatively impacts the mental health of both adults (Cleveland & Rousseau, 2013) and children (Kronick et al, 2015;Kronick, Rousseau, & Cleveland, 2016;. These findings are consistent with studies conducted in multiple other countries (Bosworth, 2016).…”
Section: Symbolic Violence Disempowerment and Mental Healthsupporting
confidence: 89%
“…For the remaining three studies, Robjant, Robbins & Senior, 2009 (referred to as Robjant 2009) analysed asylum seekers in the UK; Ichikawa, Nakahara & Wakai, 2006 (referred to as Ichikawa 2006) analysed asylum seekers in Japan, and Cleveland & Rousseau, 2013 (referred to as Cleveland 2013) analysed asylum seekers in Canada.…”
Section: Methodsmentioning
confidence: 99%
“…For Canada, Cleveland 2013 provided general information about living conditions in Canadian detention centres. The detention centres were prisons, men and women were held in separate wings, there were virtually no activities, and only primary health care was provided.…”
Section: Methodsmentioning
confidence: 99%